Evaluation of shale volume and effective porosity using larionov and archie equations from wire-line logs, Niger delta Nigeria - Mfoniso U. Aka; Johnson Cletus Ibuot; Francisca N. Okeke (International Journal of Advances in Applied Sciences, 2019)
In Niger Delta region of Nigeria, reservoirs are mostly loose and unstratified sands to hold fluids. In this paper, three different wells in central Niger Delta were assessed for shale volume and actual porosity. The results of the analysis delineate the presence of sand, sand-shale and shale formations. Hydrocarbon prospecting was found to be strong in sand, moderate in sandshale and shallow in shale respectively. However, existent of shale lessens effective porosity and water saturation of the rock formations. The extent of the formation extends from 1300 to 2500 m. Shale volume and actual porosity values extend from 0.00 to 0.302 dec and 0.047 to 0.302 dec which decrease with increasing depth. Comparably, the water saturation and water resistivity extend from 0.432 to 0.779 dec and 0.106 to 2.918 Ohm respectively. These values of actual porosity are strong in sand, moderate in sand-shale and shallow in shale formations. The results from this assessment proof well log a vital and easier tool in assessing of reservoir properties.